Meta‐analysis of global livestock urine‐derived nitrous oxide emissions from agricultural soils. (13th February 2020) - López‐Aizpún, Maria; Horrocks, Claire A.; Charteris, Alice F.; Marsden, Karina A.; Ciganda, Veronica S.; Evans, Jess R.; Chadwick, David R.; Cárdenas, Laura M.
Abstract: Nitrous oxide (N2 O) is an air pollutant of major environmental concern, with agriculture representing 60% of anthropogenic global N2 O emissions. Much of the N2 O emissions from livestock production systems result from transformation of N deposited to soil within animal excreta. There exists a substantial body of literature on urine patch N2 O dynamics, we aimed to identify key controlling factors influencing N2 O emissions and to aid understanding of knowledge gaps to improve GHG reporting and prioritize future research. We conducted an extensive literature review and random effect meta‐analysis (using REML) of results to identify key relationships between multiple potential independent factors and global N2 O emissions factors (EFs) from urine patches. Mean air temperature, soil pH and ruminant animal species (sheep or cow) were significant factors influencing the EFs reviewed. However, several factors that are known to influence N2 O emissions, such as animal diet and urine composition, could not be considered due to the lack of reported data. The review highlighted a widespread tendency for inadequate metadata and uncertainty reporting in the published studies, as well as the limited geographical extent of investigations, which are more often conducted in temperate regions thus far. Therefore, here we give recommendations for factors that are likely to affect the EFs and should be included in all future studies, these include the following: soil pH and texture; experimental set‐up; direct measurement of soil moisture and temperature during the study period; amount and composition of urine applied; animal type and diet; N2 O emissions with a measure of uncertainty; data from a control with zero‐N application and meteorological data. Abstract : Meta‐analysis of published data on emissions factors from urine revealed that animal type, soil pH and mean air temperature had significant effects on N2 O emissions. We also identified a lack of reporting of key factors with the potential to impact emissions factors so their effect on N2 O emissions could not be determined, for example, soil temperature, soil moisture and urine composition. There was also an under representation of certain geographical regions within the literature.